Salinity Impact on Yield, Water Use, Mineral and Essential Oil Content of Fennel (Foeniculum vulgare Mill.) - Ali Ünlükara; Donald Suarez; Engin Yurtseven; Gülüzar Semiz; İsa Telci (Journal of Agricultural Sciences)
The experimental study was carried out to determine the effects of salinity on water consumption, plant height, fresh and seed yields, biomass production, ion accumulation and essential oil content of fennel (Foeniculum vulgare Mill.) under greenhouse conditions. The experiment was conducted with a fully randomized factorial design with five replications. Saline waters (0.25, 1, 2, 4, 6, 8, 10 and 12 dSm-1) were composed using NaCl and CaCl2 salts keeping SAR value under than 1. Increasing salinity levels led to a decrease in water consumption, plant height, fresh yield, biomass production, seed yield, 1000-grain (seed) yield and Mg accumulations in leaves. We calculated a threshold soil salinity for fennel (Foeniculum vulgare Mill.) of 2.64 dSm-1 (salinity at which yield starts to decrease) with slope of 4.5% (yield decline per unit increase in EC). These results suggest that fennel is moderately sensitive to salinity.